PENGARUH PENGETAHUAN PRODUK, PERSEPSI RESIKO DAN PERSEPSI MANFAAT TERHADAP MINAT MENGUNAKAN LAYANAN GO PAY PADA PELANGGAN GO JEK - Ady Achadi; Hari Winarto (FEB UNWIKU PURWOKERTO, 2020)
The purpose of this study was to analyze the significant effect of product knowledge, perceived risk and perceived benefits on the interest in using Go Pay services for Gojek customers. In this study, a survey was conducted of 100 Go Pay service users provided by Go Jek, then the data obtained were analyzed using multiple linear regression. Based on the results of data analysis, it was found that there was a significant effect of product knowledge on interest in using Go Pay services as evidenced by the significance value obtained of 0.000 <alpha of 0.05, there was a significant effect of risk perception on interest in using Go Pay services as evidenced by the significance value obtained is 0.019 <from alpha of 0.05 and there is a significant effect of perceived benefits on the interest in using Go Pay services as evidenced by the significance value obtained of 0.000 <alpha of 0.05. With these results, an implication can be made that the Go Jek application provider must be able to clearly and easily understand the features that they will launch in the Go Pay service, so that users can understand the risks and benefits they will receive from using the Go Pay service. . This may also apply to companies that will launch e-wallet services.